The HIT Report from KLAS: CPOE Usage 2002, The Realities of Computerized Physician Order Entry in 2002 - KLAS (ElectronicHealthcare, 2003)
A previous KLAS study found that 75% of acute care organizations were considering either implementing Computerized Physician Order Entry (CPOE) or augmenting an existing CPOE with wireless. Other recent articles report a rather wide range of observations regarding order entry automation, physician use and CPOE benefits. This heightened interest in CPOE has created a "need to know" more about CPOE: separating fact from fiction and hype from reality, as to the who, what, when, where and why of CPOE.